Directional Dicke Subradiance with Nonclassical and Classical Light Sources - Bhatti, Daniel; Schneider, Raimund; Oppel, Steffen; von Zanthier, Joachim (Physical Review Letters, 2018)
We investigate Dicke subradiance of N >= 2 distant quantum sources in free space, i.e., the spatial emission patterns of spontaneously radiating noninteracting multilevel atoms or multiphoton sources, prepared in totally antisymmetric states. We find that the radiated intensity is marked by a full suppression of spontaneous emission in particular directions. In resemblance to the analogous, yet inverted, superradiant emission profiles of N distant two-level atoms prepared in symmetric Dicke states, we call the corresponding emission patterns directional Dicke subradiance. We further derive that higher-order intensity correlations of the light emitted by statistically independent thermal light sources display the same directional Dicke subradiant behavior and show that it stems from the same interference phenomenon as in the case of quantum sources. We finally present measurements of directional Dicke subradiance for N = 2,...,5 distant thermal light sources corroborating the theoretical finding

Generation of N00N-like interferences with two thermal light sources - Bhatti, Daniel; Classen, Anton; Oppel, Steffen; Schneider, Raimund; von Zanthier, Joachim (European Physical Journal D, 2018)
Measuring the Mth-order intensity correlation function of light emitted by two statistically independent thermal light sources may display N00N-like interferences of arbitrary order N = Ma center dot 2. We show that via a particular choice of detector positions one can isolate M-photon quantum paths where either all M photons are emitted from the same source or Ma center dot 2 photons are collectively emitted by both sources. The latter superposition displays N00N-like oscillations with N = Ma center dot 2 which may serve, e.g., in astronomy, for imaging two distant thermal sources with Ma center dot 2-fold increased resolution. We also discuss slightly modified detection schemes improving the visibility of the N00N-like interference pattern and present measurements verifying the theoretical predictions.

Quantum imaging with incoherently scattered light from a free-electron laser - Schneider, Raimund; Mehringer, Thomas; Mercurio, Giuseppe; Wenthaus, Lukas; Classen, Anton; Brenner, Gunter; Gorobtsov, Oleg; Benz, Adrian; Bhatti, Daniel; Bocklage, Lars; Fischer, Birgit; Lazarev, Sergey; et al. (Nature Physics, 2018)
The advent of accelerator-driven free-electron lasers (FEL) has opened new avenues for high-resolution structure determination via diffraction methods that go far beyond conventional X-ray crystallography methods(1-10). These techniques rely on coherent scattering processes that require the maintenance of first-order coherence of the radiation field throughout the imaging procedure. Here we show that higher-order degrees of coherence, displayed in the intensity correlations of incoherently scattered X-rays from an FEL, can be used to image two-dimensional objects with a spatial resolution close to or even below the Abbe limit. This constitutes a new approach towards structure determination based on incoherent processes(11,12), including fluorescence emission or wavefront distortions, generally considered detrimental for imaging applications. Our method is an extension of the landmark intensity correlation measurements of Hanbury Brown and Twiss(13) to higher than second order, paving the way towards determination of structure and dynamics of matter in regimes where coherent imaging methods have intrinsic limitations(14).

Simulating the photon stream of a real thermal light source - Schneider, Raimund; Biernoth, Christoph; Hölzl, Johannes; Pscherer, Andre; von Zanthier, Joachim (Applied Optics, 2018)
We present a computer algorithm capable of simulating the photon stream and the corresponding temporal photon statistics of thermal light sources. The algorithm implements realistic experimental conditions, incorporating the relevant parameters of the source as well as of the detection process. The code is verified by comparing the temporal photon autocorrelation function computed from the simulations to the one measured with a real thermal light source. In view of the renewed interest for intensity interferometry in astronomy and the life sciences, such simulations become increasingly relevant. (C) 2018 Optical Society of America

Superresolving Imaging of Arbitrary One-Dimensional Arrays of Thermal Light Sources Using Multiphoton Interference - Classen, Anton; Waldmann, Felix; Giebel, Sebastian; Schneider, Raimund; Bhatti, Daniel; Mehringer, Thomas; von Zanthier, Joachim (Physical Review Letters, 2016)
We propose to use multiphoton interferences of photons emitted fromstatistically independent thermal light sources in combination with linear optical detection techniques to reconstruct, i.e., image, arbitrary source geometries in one dimension with subclassical resolution. The scheme is an extension of earlier work [S. Oppel et al., Phys. Rev. Lett. 109, 233603 (2012)], where N regularly spaced sources in one dimension were imaged by use of the Nth-order intensity correlation function. Here, we generalize the scheme to reconstruct any number of independent thermal light sources at arbitrary separations in one dimension, exploiting intensity correlation functions of order m >= 3. We present experimental results confirming the imaging protocol and provide a rigorous mathematical proof for the obtained subclassical resolutio